Ocular dirofilariasis - Nath Reema; Gogoi Rajen; Bordoloi Narayan; Gogoi Tapan (Wolters Kluwer Medknow Publications, 2010)
Dirofilaria is a parasite of domestic and wild animals that can infect humans accidentally. It is being reported in increasing numbers from Mediterranean countries like Italy. In India this infection is occasionally being reported. We report three cases of ocular dirofilariasis from the state of Assam presenting as periorbital and subconjunctival cysts. The parasites were identified as Dirofilaria repens. The purpose of this article is to take note of this emerging zoonosis in Assam; also to review literature in the cases reported.